KODE ETIK PENDIDIK MENURUT IBNU JAMA’AH - Syabuddin Gade (Majelis Pendidikan Daerah (MPD) Aceh dan Universitas Syiah Kuala, 2015)
This study - through content and descriptive analyses - seeks to explore Ibn Jama'ah thought about his ethical code educators in Tazkirah al-Sami'. To that end, the book Tazkirah al-Sami' will be discussed in depth. The study obtained that the code of ethics educators in Tazkirah al-Sami' generally consists of three categories, namely; The first, code of personal ethics educator, consists of 12 chapters sequentially explain the relationship between educator and God (verse 3); glorify science (3 verses); ascetic (4 verses); the use of science (paragraph 2); away from the action and place reprehensible (fourth paragraph); implement and support the symbols of religion (4th paragraph); maintaining practice sunnat (4 verses); norms of social interaction (paragraph 13); purify themselves of bad moral character and cultivate commendable (second paragraph); the deepening of knowledge (paragraph 6); learn from the juniors (second paragraph); and write (4 verses). Second, the code of ethics educators in teaching, which consists of twelve chapters sequentially explained about: preparation before teaching (3rd paragraph), praying and teaching behavior (paragraph 7), classroom management (paragraph 5), the initial act of teaching (4 verses ), hierarchy and transfer of knowledge (paragraph 6), voice teacher and an opportunity to ask (third paragraph), the function of discussion in Majlis (fourth paragraph), the role of educators in the discussion (paragraph 3); fair, intelligent and fair (paragraph 6), an appreciation of non-regular students (second paragraph), the cover learning (6 verses) and professional (third paragraph). Third, codes of conduct interaction with the student teachers, which consists of fourteen chapters, each associated with; the purpose of teaching (verse 9); directing learning objectives (3 verses); motivator (paragraph 6); treat students like their own children (4 verses); attention to student ability and openness delivery of science (4 verses); earnest and convincing (fourth paragraph); ability test (paragraph 5); reward, motivation and learning groups (paragraph 3); the intensity and scale of learning priorities (paragraph 3); learning resources (paragraph 4); to be fair and considerate (4 verses); monitoring and warning (paragraph 5); moral and material support (paragraph 6); humble and meek (fourth paragraph).